2015
DOI: 10.1016/j.tetlet.2015.01.142
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological evaluation of β-carboline dimers based on the structure of neokauluamine

Abstract: The design, synthesis and biological evaluation (anticancer and antimalarial activity) of bis-β-carbolines, based on the structure of the naturally occurring alkaloid neokauluamine, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Coldhman and co‐workers reported the Synthesis and anti‐tubercular activity of monomeric ligands of bis‐β‐carboline dimers (Figure 14) against MTB (H 37 Rv) strain. Among the series of dimeric carbolines, compounds 91 and 92 were found to be more potent than manzamine A (1.5 μg mL −1 ) [58] …”
Section: β‐Carboline Derivatives As Anti‐tb Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coldhman and co‐workers reported the Synthesis and anti‐tubercular activity of monomeric ligands of bis‐β‐carboline dimers (Figure 14) against MTB (H 37 Rv) strain. Among the series of dimeric carbolines, compounds 91 and 92 were found to be more potent than manzamine A (1.5 μg mL −1 ) [58] …”
Section: β‐Carboline Derivatives As Anti‐tb Agentsmentioning
confidence: 99%
“…Coldhman and co‐workers reported that structurally simplified analogs of β‐carboline as promising anti‐tubercular agents [58] . In this view, Moreira, and co‐workers synthesized and evaluated nine compounds belonging to a series of guanidinium or amino group derivatives of β‐carboline by Pictet‐Spengler reaction using L‐tryptophan as a starting material.…”
Section: β‐Carboline Derivatives As Anti‐tb Agentsmentioning
confidence: 99%
“…[39] Inspired by the uniquea nd interesting biological profile of neokauluamine, an aturally occurring alkaloid, Chatwichien et al reported the facile synthesis of biscarbolines 55 and 57 from ar eductive amination of linker diamines with Kumujian C (7), as outlined in Scheme 21. [40] This reaction was accompanied by the formation of monomeric b-carboline derivatives that contained ad iamine chain (56 and 58). Furthermore, monomeric as well as dimeric b-carboline derivatives (55)(56)(57)(58) were screenedf or their anticancer and antimalarial properties and the biological assay revealed that bis-b-carboline derivatives were more potent than the corresponding monomeric derivatives against both cancer and malarialcell lines.…”
Section: Synthesis Of C1-tethered B-carboline Frameworkmentioning
confidence: 99%
“…Dimeric β-carboline 1 exhibited comparable potency to manzamine A 3 and significantly greater cytotoxicity than the corresponding monomer 2 in each of the NSCLC cell lines. 17 The relative cytotoxicity of 1 was consistently greater than that of monomer 2 in NSCLC cells compared to IMR90 (human lung fibroblast) cells. These results support the importance of the dimeric structure of 1 , and suggest that these dimeric structures could represent lead compounds for the development of new NSCLC therapeutics.…”
mentioning
confidence: 91%
“…14 β-carbolines exhibit broad biological activity and exhibit antimalarial, anticancer, antiviral and anti-inflammatory properties. 15,16 We have recently reported that dimeric β-carbolines 17 exhibit significantly enhanced cytotoxicity relative to their monomeric counterparts against multiple cancer cell lines, including NSCLC, prompting us to study the mechanism of action of the cytotoxicity of these dimeric β-carbolines. We describe herein the preparation of a novel lysosomotropic agent, dimeric β-carboline 1 (Figure 1), its evaluation against six NSCLC cell lines, and preliminary results on the mechanism of action of 1 .…”
mentioning
confidence: 99%